La Jolie Fille de Perth de Bizet ou comment trahir et honorer Walter Scott - Gilles Couderc (Revue LISA)
What remains of Walter Scott’s Fair Maid of Perth in Bizet’s 1867 Jolie Fille de Perth, an opera in 4acts on a libretto by Jules Adenis and Vernoy de Saint-Georges? Not much when compared to other Scott-inspired operas. Little historical context or local colour, even in Bizet’s music. Some characters remotely linked to Scott in a libretto that mostly abides by the rules of French opera or opéra-comique of the time and recycles the dramatic ingredients favoured by Saint-Georges, a purveyor of libretti for opera or the ballet second only to Scribe, who engendered such international successes as Flotow’s Martha and Balfe’s Bohemian Girl, whose gipsy, long before his Carmen, haunts Bizet’s “Scottish” opera. Yet the work pays indirect homage to Scott, whose historical novels contributed to the birth of the French “grand opera”, by rewriting scenes or situations drawn from Scott. In spite of borrowing freely from French grand opera and opéra-comique, Bizet here attempts to find his own musical expression and his opera reflects aspects of Second Empire French society and the roles it assigned to women, before the appearance of his revolutionary Carmen on the stage.